Recalcitrant Industrial Wastewater Treatment Using Fenton and Photo-Fenton Oxidation: A Comparison Study - Wijayanti, Karima Anggita; Hakika, Dhias Cahya; Setyawan, Martomo; Suhendra; Amal, Ikhlasul; Biddinika, Muhammad Kunta (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2024)
The growth rate in agro-industrial sectors has both positive and negative effects on technological, social, and economic development. Agro-industry production generates substantial volumes of wastewater, primarily from the aqueous discharges of its manufacturing processes. Some of this wastewater contains harmful pollutants that endanger human life, health, and the sustainability of the environment and ecosystem. For example, wastewater from the bioethanol industry contains high concentrations of organic pollutants and recalcitrant compounds, with COD and BOD values exceeding 50,000 mg/L and 30,000 mg/L, respectively. The Fenton process is an oxidation method that generates hydroxyl radicals through the reaction between H2O2 and Fe2+ ions. These hydroxyl radicals are highly effective at breaking down recalcitrant compounds. In this study, a comparative analysis of recalcitrant wastewater treatment using Fenton and photo-Fenton oxidation processes was conducted. The effects of dilution factors, or initial concentrations of recalcitrant wastewater (1:25, 1:50, and 1:75), were examined. Higher dilution ratios enhanced the degradation of COD and BOD levels in wastewater, with the optimal dilution factor for both processes being 1:75. Under optimal conditions, the removal efficiencies for COD, BOD, potassium, and phenol were in the range of 72.29-99.99%. The photo-Fenton process demonstrated higher removal efficiency compared to the Fenton process. The conclusion from this study suggests that the photo-Fenton process could be successfully employed as an advanced treatment method for effectively breaking down recalcitrant wastewater. These findings could be useful for adapting these processes to field-scale applications.